2010
DOI: 10.2478/s11696-010-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical variability of Artemisia herba-alba Asso essential oils from East Morocco

Abstract: Chemical compositions of 16 Artemisia herba-alba oil samples harvested in eight East Moroccan locations were investigated by GC and GC/MS. Chemical variability of the A. herba-alba oils is also discussed using statistical analysis. Detailed analysis of the essential oils led to the identification of 52 components amounting to 80.5–98.6 % of the total oil. The investigated chemical compositions showed significant qualitative and quantitative differences. According to their major components (camphor, chrysanthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 31 publications
0
24
2
Order By: Relevance
“…The intraspecific chemovariation of the essential oils isolated from the aerial parts of the two Artemisia species were also observed in several countries and also in the southern part of Tunisia . A .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The intraspecific chemovariation of the essential oils isolated from the aerial parts of the two Artemisia species were also observed in several countries and also in the southern part of Tunisia . A .…”
Section: Resultsmentioning
confidence: 69%
“…herba‐alba and A . campestris has been widely investigated . In Tunisia, the chemical variability of the essential oils extracted from A .…”
Section: Introductionmentioning
confidence: 99%
“…Many works showed the richness in terpenoids of A. herba-alba, like monoterpene hydrocarbons (Behtari, 2012), oxygenated monoterpenes (Hudaib and Aburjai, 2006) and sesquiterpenes (Laid, 2008;Paolini, 2010 (Soliman, 2007). Miresmailli et al (2006) and Verma (2012) pointed out the presence of monoterpenes in rosemary whereas Zhang et al (2014) reported its richness in diterpenoid and triterpenoid glycosides.…”
Section: Figurementioning
confidence: 99%
“…Curcumen-15-al has been reported for the first time in Artemisia herba-alba oil and the correspondent oil should be considered as a new chemotype. α-Thujone has been reported as the major constituent of the Artemisia herba-alba essential oil originating from Tunisian semi-arid and south region (Akrout, 2004;Kadri et al, 2011), Jordan (Hudaib and Aburjai, 2006), Algeria (Belhatta et al, 2014), Morocco (Paolini et al, 2010) and Israel (Fleisher et al, 2002). This monoterpenic cetone confers to this plant its characteristic smell of Mentha and its bitter taste.…”
Section: Resultsmentioning
confidence: 99%